2011
DOI: 10.1038/nrneph.2011.170
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of novel prognostic biomarkers in patients on hemodialysis

Abstract: Prognosis, risk stratification and monitoring the effects of treatment are fundamental elements in the decision-making process when implementing prevention strategies for chronic kidney disease. The use of biomarkers is increasingly proposed as a method to refine risk stratification and guide therapy. In this Review, we present basic concepts regarding the validation of biomarkers and highlight difficulties inherent to the identification of useful new biomarkers in patients on hemodialysis. We focus on prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 99 publications
(119 reference statements)
1
37
0
3
Order By: Relevance
“…2 TnT, BNP, and CRP levels individually reflect a unique pathophysiological pathway in cardiovascular disease, and may identify different subpopulations at increased risk of mortality. Thus, it is not surprising that simultaneous assessment of these 3 biomarkers yielded independent and complementary prognostic information.…”
Section: Multimarker Scorementioning
confidence: 99%
See 1 more Smart Citation
“…2 TnT, BNP, and CRP levels individually reflect a unique pathophysiological pathway in cardiovascular disease, and may identify different subpopulations at increased risk of mortality. Thus, it is not surprising that simultaneous assessment of these 3 biomarkers yielded independent and complementary prognostic information.…”
Section: Multimarker Scorementioning
confidence: 99%
“…40 However, echocardiography is often a limited resource and may not be routinely available. 2 Several studies have suggested that TnT (or TnI) and BNP (or…”
Section: Study Limitationsmentioning
confidence: 99%
“…However, conventional risk stratification tools remain imprecise in establishing cardiovascular prognoses in this population [2]. Furthermore, traditional Framingham risk factors explain only a fraction of the high frequency of cardiovascular disease and death among hemodialysis patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 is a major proinflammatory mediator well characterized in the orchestration of the inflammatory response following acute renal insult 4,5 and has been shown to be a superior marker in renal patients compared with other proinflammatory candidates, such as the systemic inflammatory marker C-reactive protein. [6][7][8][9] On the other hand, IL-10, while not as established in kidney injury, is appreciated to be a prototypical anti-inflammatory cytokine that carries out the critical function of modulating inflammation. 10,11 Accordingly, IL-6 has been suggested to exacerbate renal injury, 12,13 while IL-10 has been shown to confer protective effects.…”
mentioning
confidence: 99%